Profiles of Racial Socialization Among African American Parents: Correlates, Context, and Outcome - Caughy, Margaret O’Brien (J Child Fam Stud, 2010)
Self report and observational data on racial socialization practices in a sample of 218 African American parents of young children were used to determine whether or not parents could be characterized in terms of their pattern of racial socialization practices. Parents fell into four groups: silence about race, emphasis on cultural socialization, emphasis on cultural socialization and coping strategies, or a balanced approach. Silence about race was more common among parents of boys, whereas an emphasis on cultural socialization was more common among parents of girls. Silence about race was less common in neighborhoods with high levels of negative social climate, and a combination of cultural socialization with coping strategies for discrimination was more common in neighborhoods with high neighborhood potential for community involvement with children. The coping emphasis/cultural socialization approach was associated with significantly lower child problem behavior, although some gender differences were evident. A cultural socialization emphasis was associated with higher cognitive scores among girls, and a combination of cultural socialization, coping with discrimination, and promotion of mistrust was associated with higher cognitive scores among boys. Implications of this profile approach for the study of racial socialization practices in ethnic minority families are discussed.